The Diagnostic Potential of SHOX2 and RASSF1A DNA Methylation in Early Lung Adenocarcinoma - Gao, Hong; Yang, Jun; He, Lu; Wang, Wei; Liu, Yanhong; Hu, Yue; Ge, Meiling; Ding, Jie; Ye, Qing (Frontiers in Oncology, 2022)
Objective: Methylation of the promoters of SHOX2 and RASSF1A are potentially informative biomarkers for the diagnosis of early lung adenocarcinoma (LUAD). Abnormal methylation of SHOX2 and RASSF1A promoters may promote the occurrence and facilitate the development of LUAD. Materials and Methods: We evaluated DNA methylation in samples from 54 patients with early LUAD and 31 patients with benign lung nodules for the discovery set. The DNA methylation sequencing, mRNA sequencing, and clinical data for patients with LUAD were obtained from The Cancer Genome Atlas, and served as a validation set. We evaluated the diagnostic potential of a SHOX2 and RASSF1A combined promoter methylation assay for detection of early LUAD in the discovery set and we explored associations of promoter methylation of SHOX2 and RASSF1A with tumor stage in the validation set. Pathways enriched between tumor and normal samples of methylation-positive patients in both sets were compared. Results: In the discovery set, the sensitivity of the combined promoter methylation assay on tumor samples was 74.07%, the sensitivity on paired tumor and paracancerous samples was 77.78%, and the specificities in both contexts were 100%. The methylation-positive patients had clinicopathologic features including older age, larger tumors, deeper invasion, and higher Ki-67 expression. In the validation set, promoter methylation of both genes was significantly higher in stage I LUAD samples than in normal samples. The methylation level of SHOX2 gradually decreased with the progress of tumor, while RASSF1A remained hypermethylated at all tumor stages. In both sets, SHOX2 promoter hypermethylation was associated with higher SHOX2 expression, while RASSF1A hypermethylation was associated with lower RASSF1A expression. The combined methylation-positive patients exhibited upregulation of folate acid metabolism and DNA instability, and downregulation of vasoconstriction, cell growth and differentiation, and regulation of metabolism. Conclusion: The combined promoter methylation assay for SHOX2 and RASSF1A can be used for screening and diagnosis of early LUAD, with good sensitivity and specificity. The promoter methylation of SHOX2 and RASSF1A was associated with their abnormal mRNA expression, and affected DNA replication and repair, apoptosis, and aspects of the tumor microenvironment in patients with LUAD.